2003
DOI: 10.1103/physrevb.67.064516
|View full text |Cite
|
Sign up to set email alerts
|

Zn-neighbor Cu NQR in Zn-substitutedYBa2Cu3O7

Abstract: We studied local electronic states near Zn in optimally doped YBa2(Cu1−xZnx)3O 7−δ and underdoped YBa2(Cu1−xZnx)4O8 via satellite signals of plane-site Cu(2) nuclear quadrupole resonance (NQR) spectra. From the relative intensity of Cu NQR spectra, the satellite signals are assigned to Zn-neighbor Cu NQR lines. The Cu nuclear spinlattice relaxation time of the satellite signal is shorter than that of the main signal, which indicates that the magnetic correlation is locally enhanced near Zn both for the underdo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
3
5

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 72 publications
6
68
3
5
Order By: Relevance
“…This line was discovered by Williams et al [2] and was confirmed by Itoh et al [3,4], while it is also possibly visible in an earlier report by Yamagata et al [5]. WK argue that this resonance arises from the four Cu first neighbors (Cu NN ) of each Zn impurity in CuO 2 planes.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…This line was discovered by Williams et al [2] and was confirmed by Itoh et al [3,4], while it is also possibly visible in an earlier report by Yamagata et al [5]. WK argue that this resonance arises from the four Cu first neighbors (Cu NN ) of each Zn impurity in CuO 2 planes.…”
Section: Introductionsupporting
confidence: 56%
“…We show here that the conclusions of WK cannot be sustained by their NQR measurements. Other comments on the work of WK, complementary those presented here, can be found in the comprehensive study of Itoh et al [4].…”
Section: Introductionmentioning
confidence: 93%
“…These results remind us of the in-plane impurity-substitution effect [17]. The nuclear moments close to an impurity show nonexponential relaxation, because of random impurity distribution.…”
Section: B Nuclear Spin-lattice Relaxationmentioning
confidence: 72%
“…The pseudogap around the single impurity has been investigated by the NMR measurements. [64][65][66][67] We discuss the relevance of our results for these experiments. In this section, we adopt the self-consistent T-matrix approximation for N = 31 × 31 sites.…”
Section: Pseudogap Around Single Impuritymentioning
confidence: 99%